Development of Mobile Learning Based on Adobe Flash Professional CS6 on Android Material - Deswalman, Deswalman; Farni, Evi Ramna (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2016)
The aim of this research is to develop a mobile learning application using Android-based Adobe Flash Professional CS6 on mechanical wave characteristics material for class -characteristics of mechanical waves for class XI high school. This type of research is research and development with the ADDIE development model. This model involves the stages of analysis, design, develop, implementation and evaluation. The instruments used were a material and media expert validation questionnaire conducted by a team of experts as well as a student perception questionnaire which was tested in one of the XI high school classes. The data analysis technique in the form of suggestions by the validator is carried out in a qualitative descriptive manner. Meanwhile, validation questionnaire scores and student perception questionnaires were carried out using descriptive statistics. The mobile learning application developed has .apk and .swf formats which can be run on Android smartphones and PC/laptops. The score resulting from students' perceptions of mobile learning applications is 50.35 and is categorized as very good.